PELATIHAN PEMBUATAN HAND SANITIZER ALAMI DARI DAUN SIRIH DAN JERUK NIPIS - Arezqi Tunggal Asmana; Minhatin Nisaatus Sholikhah; Juniati Ilma Muslikha; Muhammad Fikhrul Umam (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2022)
Corona virus or so-called Covid-19 is an infectious disease caused by acute respiratory syndrome coronavirus 2. The spread of Covid-19 in Ngayung village is currently experiencing a significant decline, in connection with the government's program to tighten health protocols. The use of masks, washing hands and complying with other health protocols are very prioritized. In relation to hand washing, Hand Sanitizer is a personal protective device from germs and bacteria, besides being practical to carry and use, it is also easy to make. As we know, the manufacture of Hand Sanitizer usually relies more on chemicals which are relatively expensive and difficult to find. It is different from the presence of betel leaf and lime as an abundant Hand Sanitizer in Ngayung Village. This prompted us from Unisda to innovate in the manufacture of Hand Sanitizer from natural ingredients that are easy to make, safe, and easy to find. With this training, people can be more aware of cleanliness and better protect themselves and their families from viruses and the threat of disease.